Morphological Characteristics of Normal Foveal Avascular Zone by Optical Coherence Tomography Angiography. (19th August 2020) - Eldaly, Zeiad; Soliman, Wael; Sharaf, Mohamed; Reyad, Ali Natag
Abstract : Purpose . To provide quantitative measurements for the foveal avascular zone (FAZ) and to describe its morphological characteristics by optical coherence tomography angiography (OCT-A). Design . Cross-sectional observational case series. Methods . Healthy volunteers were recruited and evaluated using Triton-DRI SS-OCT Angiography. A 4.5 × 4.5 mm square was evaluated by OCT-A center around the fovea. Superficial and deep capillary plexus were identified, and different quantitative measurements were conducted along with categorization of the FAZ pattern. Results . Eighty-two eyes (41 volunteers) were evaluated. Mean age was 30.59 ± 7.6 years (23–42 years). Mean subcentral retinal thickness was 200.1 ± 5.66 um (192–210 um). The number of terminal vessels was variable (range, 8–11). Mean maximum terminal vessel-to-vessel intervening distance was 527.8 ± 60.3 um (471–674 um). Mean minimum terminal vessel-to-vessel intervening distance was 296.7 ± 45.8 um (233–373 um). Mean maximum horizontal diameter of FAZ (superficial) was 716.17 ± 124.09 um, while mean maximum vertical diameter of FAZ (superficial) was 667.76 ± 131.28 um. Mean maximum horizontal diameter of FAZ (deep) was 823.19 ± 144.92 um, while mean maximum vertical diameter of FAZ (deep) was 794.03 ± 150.28 um. OCT-A detected different FAZ patterns; horizontally oval configuration in 32 eyes (39%), rounded configuration in 24 eyes (29.3%), pentagon configuration in 14 eyes (17.1%), and vertically oval and nonspecific configuration in 6 eyes each (7.3%). Conclusion . OCT-A could efficiently provide both quantitative and qualitative assessment of normal FAZ; such characterizations were difficult by standard FAZ assessment procedures like FFA.